Pendampingan Pembuatan Ecoprint sebagai Upaya Menumbuhkan Kreativitas dan Kesadaran Lingkungan pada Siswa Kelas V Sekolah Dasar di Desa Wonorejo Tulungagung - Rohmatus Syafi’ah; Mukhammad Zainul Muttaqin; Siti Anisa Rahmi; Nimas Ayu Mufliha Sati (LP3M IAIFA Kediri, 2026)
The abundant natural resources found in rural areas are often left untapped as creative and productive media for empowering and educating the younger generation. This mentoring activity aimed to foster creativity, introduce eco-friendly art, and cultivate environmental awareness among fifth-grade elementary school students in Wonorejo Village through the ecoprint technique. Ecoprint is a method of transferring natural motifs from leaves and flowers onto fabric surfaces using the pounding technique, entirely free from synthetic chemicals, making it a safe, affordable, and sustainable educational medium. The activity was carried out from July 21-23, 2025, at SDN 1, SDN 2, and SDN 3 Wonorejo on consecutive days, involving all fifth-grade students from the three schools as participants. Implementation followed three structured stages: (1) conceptual introduction to ecoprint and environmental awareness; (2) technique demonstration by the community service team; and (3) independent and creative practice by students. The results showed that all participants successfully completed one uniquely patterned natural-motif tote bag, demonstrating active engagement at every stage from exploring natural materials around the school grounds to finalizing their works. The diverse motifs produced reflected each student's individual creative expression, while simultaneously affirming that local natural resources hold meaningful potential as a source of creativity for elementary school-aged children. This activity provides evidence that community mentoring grounded in local natural potential is an effective model of community service that can be adopted in other villages with similar characteristics.